Sanitary Conditions and Inmates’ Knowledge and Attitude towards Hygiene Practices in a Maximum-Security Prison in Oyo State, Southwest Nigeria (Nigerian Journal of Health Sciences, 2023)
Context: The study was conducted in a maximum‑security prison in southwest Nigeria, where inmates were held in lawful custody by a court of competent jurisdiction. The inmates are vulnerable, and their health is conditioned not only on their nutrition and health‑care services but also on available water and sanitation services, personal and collective hygiene behaviour, within the prison environment.Aim: The study assessed the living and sanitary conditions and hygiene practices of inmates in a maximum‑security prison in Nigeria.Settings and Design: The study was descriptive, cross‑sectional in design and elicited information on knowledge, attitude and hygiene practice of consented prison inmates.Methods: The questionnaire response was 94.8% and was identified through a multistage sampling technique and inmates were stratified by detention status with the minimum sample allocated by the proportional to size method. Systematic sampling was used for serial recruitment without replacement. The data collection tool was a validated, semi‑structured, interviewer‑administered questionnaire.Statistical Analysis Used: Knowledge and attitudes were measured on a 24‑ and 55‑point scales and rated as poor (≤11) and good (>11); negative (≤33) and positive (>33), respectively. Summary data were presented by descriptive, Chi‑square and logistic regression at P < 0.05.Results: Inmates mean age was 31.6 ± 8.2 years and mostly, males (98.3%) with 47.2% and 50.8% respectively married and completed secondary education. The main water source to inmates was hand-dug wells, while all-male conveniences were dirty. The major illnesses were malaria, ringworm and diarrhoea. In addition, sanitary knowledge was a significant predictor of attitude towards hygiene practices (OR: 0.52, 95% CI: 0.298‑0.905).Conclusions: The good knowledge and positive attitudes of inmates contrast poor sanitary conditions, perhaps due to poor sanitation and hygiene infrastructure and overcrowding conditions.